Cape Verde : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2010)
The development policy of Cape Verde has evolved in a setting of severe structural constraints and persistent restrictions, with potential impediments to growth. The ongoing process of change adopts a transformation strategy closely linked to the consolidation of a democracy based on sound institutions. Democratic strengthening is essential and presupposes the consolidation of good governance as a key factor in any development strategy. Executive Directors consider that effective implementation of the poverty reduction and growth strategy has been made in Cape Verde.